Comparison of national and international sanitary standards regarding the proper use of antibiotics in species of aquaculture production applicable to the production of trout (Oncorhynchus mykiss) in Peru - Arellano B., Raquel (2022)
The objective of the study was to evaluate the agreement between the provisions issued by the National Fisheries Health Agency (SANIPES) with its Chilean counterpart and the principles approved by the World Organization for Animal Health (OMSA), regarding the use of antimicrobial agents in aquaculture. To do this, the national regulations regarding the use of antibiotics in aquatic species were compared with the OMSA aquatic animal health code and two Chilean regulations, a country where aquaculture is more developed in the region. The norms were taken to comparison matrices and were later analyzed. It was found that the Peruvian regulations mostly implemented the guidelines indicated in the OMSA principles for the use of antibiotics in aquaculture aimed at distributors of antimicrobials for use in fish and producers of aquatic species. On the other hand, it did not specifically contemplate the guidelines for the use of antibiotics by aquaculture health professionals or guidelines on off-label use, in the comparison of the OMSA regulations and those of Chile. The qualitative evaluation found agreement between the SANIPES regulations and the OMSA principles aimed at distributors of antibiotic products for use in fish and producers of aquatic species, but low agreement between the guidelines aimed at veterinarians. In addition, the two Chilean regulations had a more specific structure and almost fully implemented the OMSA principles compared to the Peruvian one, for which reason an improvement in the latter is suggested according to the reality of the sector.